ENKRIPSI DATA MENGGUNAKAN RSA & AES PADA APLIKASI INSTANT MESSAGING BERBASIS MOBILE - Yanuar Bimantoro; Ratih Titi Komala Sari (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
Currently communication can be through various media, one of the most favorite is the instant messaging application because it presents complete features and can be used anywhere [1]. But digital data is vulnerable to theft, one example is when an application sends data to a server can be intercepted or the server is hacked [2]. Therefore required data security system one of which is encryption [3]. The research aims to implement encryption for data security using AES and RSA algorithms combined [4]. The method to be used is that AES will encrypt the original data and then the resulting AES key will be encrypted with RSA. Based on the results of combined testing these two algorithms can process data in the form of text and images in milisekon time and can still secure the original data.